Caso de estudio: exportación de aceite esencial de maracuyá al mercado cosmético en Alemania - Navarrete Sarmiento, Briceida (2019)
This research has the purpose of making organic passion fruit oil known in the cosmetic sector, providing valuable information to the consumer, as well as demonstrating that it is a cosmetic alternative with a lot of potential in the foreign market. Beauty Nature is an enterprise that marketer and exporter of cosmetic products that is committed to ecologic and organic. Organic passionfruit seed oil is an oil extracted from the seeds thereof, with high beneficial properties for the skin, due to its composition of essential fatty acids. Our motivation to introduce our organic passion fruit seed oil is born as a result of the skin problems of redness, allergies, spots, rashes, etc., caused by the use of conventional cosmetics, in which the products are generally made a base of artificial or synthetic inputs, mostly derived from petroleum, which ends up reflecting skin aging. The research is developed in two chapters: In the first chapter, we focused on choosing and knowing the most viable destination market through the factor classification method, in addition to the PESTE analysis, which show us Germany. These analyzes were essential to determine our demand, and then to be able to study the offer and positioning in our market, in addition to understanding what our position in this market is through the competitive profile matrix. In the second chapter the marketing plan is developed in addition to our product value proposal. There are also costs incurred when the project is launched. And finally, the research findings and recommendations are presented.